The use of Cannabidiol in the treatment of Alzheimer`s Disease: What are the main pharmacological effects attributed to Cannabidiol relevant to the treatment of Alzheimer`s Disease? (Research, Society and Development, 2026)
Neurodegenerative diseases represent one of the major global public health challenges, especially due to population aging. Among them, Alzheimer’s disease (AD) stands out for its high prevalence and severe impact on the quality of life of patients and their families. Characterized by the progressive loss of neurons and the abnormal accumulation of β-amyloid (Aβ) and Tau proteins, AD involves complex mechanisms of neuroinflammation, oxidative stress, and synaptic dysfunction. In this context, cannabidiol (CBD), a non-psychoactive phytocannabinoid derived from Cannabis sativa, has attracted growing scientific interest due to its anti- inflammatory, antioxidant, and neuroprotective properties. This study aims to analyze the main pharmacological effects and mechanisms of action of CBD in the treatment of Alzheimer’s disease through a scoping review conducted in the Google Scholar and PubMed databases, covering publications from 2010 to 2025. The results show that CBD acts on multiple molecular targets such as CB1, CB2, PPARγ, TRPV1, 5-HT1A, and GPR55, promoting a reduction in neuroinflammation, inhibition of the GSK-3β enzyme, activation of the Wnt/β-catenin pathway, decreased Aβ production and Tau phosphorylation, as well as improved synaptic homeostasis. Although there are still gaps regarding optimal dosage, long-term safety, and standardized clinical protocols, current evidence indicates that CBD is a promising and safe therapeutic alternative for managing Alzheimer’s disease, potentially slowing its progression and improving patients’ quality of life.